Entangled Production of Individuals and Organizations: A Food Systems Case Study in Service-Learning Transformations - D. Travers Scott; Sallie Hambright-Belue; Mike McGirr (Journal of Community Engagement and Scholarship, 2023)
This article presents a longitudinal case study of a collaboration between a university and a nonprofit food justice organization. Using a collective autoethnographic process, we examine a three-semester service-learning course in which each author participated as instructor or client. We use the theoretical tools of intra-action and entanglement to address the challenges of complexity in such social justice collaborations. We also deploy these tools to avoid the instrumental/functional paradigm of evaluating collaboration in terms of negative or positive effects or un/successful outcomes, focusing instead on phenomena within a system in their transformative entanglements within ongoing (re)becoming. This approach was amenable to the content of our collaboration: a systems approach to thinking about food equity. Conceiving of ongoing interrelated phenomena within a system, as opposed to discrete separate objects impacting one another, helps accommodate the complexity involved in service-learning collaborations. Author/participants include an independent farmer who also teaches architecture, a communication instructor, and the director of a regional food justice nonprofit who collaborated via a land-grant university on an applied service-learning series of classes. We describe productive transformations in food-systems activism for individuals, our institution, local organizations, and the broader community. Therefore, this article contributes not an evaluative assessment of the success or failure of a single collaboration but a longitudinal examination of how individuals, institutions, organizations, and communities change through their entanglements and intra-actions.